Analyzing the Impact of Subtitling and Transformational Leadership on Improving the Schools Learning Environment: Applied Study on Secondary Schools in Jazan Province, Saudi Arabia - waselia, Fatima ali (Journal of Posthumanism, 2025)
This study investigates the impact of subtitling and transformational leadership on the learning environment in secondary schools in Jazan Province, Saudi Arabia. The main findings indicate a positive relationship between subtitling and students’ English language skills, highlighting that exposure to subtitled media enhances comprehension and vocabulary mastery. The research utilized a cross-sectional survey methodology, collecting data from 424 students and teachers through structured questionnaires and statistical analyses, including descriptive statistics and t-tests. Implications for educational practice suggest that incorporating subtitling in classrooms can significantly improve language learning and foster a more engaging learning environment. However, challenges identified include the limited use of advanced educational resources and the need for transformational leadership qualities among school principals to effectively implement these strategies. Overall, the research emphasizes the importance of addressing educational leadership and innovative teaching methods to enhance students’ learning experiences in Jazan schools.